"We Are Aiming for Quality and Good Music": The Hebrew Orphan Asylum Harmonica band (NYC) and Music Education, 1924–1930. Issue 1 (October 2020) - Shansky, Carol L.
Once referred to as "the most maligned musical instrument on earth, " the harmonica holds an important historical place in music education as an instrument around which bands were formed, solo and ensemble competitions were held, and in some cases, careers were born. Much of this activity centered itself on city recreation programs as well as public schools. The instrument's size, low price, and relative ease of sound production were appealing for these organizations. The boys and girls that lived and studied at the Hebrew Orphan Asylum of New York City were engaged participants in these contests as well as performing in radio broadcasts of harmonica band playing. This paper examines the history of this ensemble as a representative of the incredible activity in this underresearched area of music education.